Peningkatan Kapasitas Produksi Alat Angkut Untuk Mencapai Target Produksi 5000 ton/bulan Pada Kegiatan Galian Clay Menggunakan Metode antrian pada Tambang IUP OP Jumaidi, Gunuang Sariak, Sumatera Barat. - Muhammad Deri Frasetia; Tri gamela saldy (Journals Mining Engineering : Bina Tambang, 2023)
IUP OP Jumaidi is one of the mining business licenses engaged in mining, especially mining and clay trading, which is located in Gunung Sarik Village, Kuranji District, Padang City, West Sumatra Province. Based on field observations at the IUP OP Jumaidi, the authors found that production data in December 2021 produced only 2689.57 tons, while the production target to be sent to PT Semen Padang was 5000 tons/month. The Jumaidi IUP is currently experiencing several obstacles not achieving its production target caused by several factors, including weather factors, social factors, dust, work efficiency, poor road access, and hauling time for transportation equipment. The effective working time is 160 hours/month. Meanwhile, the actual effective working time is 120 hours/month. To get optimal production results, the efficiency and capabilities of the tools used must be considered. IUP OP Jumaidi has 4 excavators and 16 trucks for Loading and Hauling activities. Based on the author's observations IUP OP Jumaidi uses 1 excavator (excavator) serving 6 trucks in 1 place, this results in not achieving the production targets set by the company, from the author's observations there are problems with the waiting time of the tool (delay) on loading 3-5 minutes which which is very different from the company's rule of 1-2 minutes. Furthermore, the problem encountered by the author is the production of the means of conveyance, which is equal to 2617.472 tons / month, the match factor is 0.043 and the actual effective working time of the digging and conveyance equipment is 70%, this is not in accordance with the company's provisions, which is equal to 80%. The actual productivity data the means of transportation is 5941,097 tons/month. The calculation of the effective working time the dumptruck is 46,75 hours. The match factor value obtained is 0.17.